Intertextuality and recontextualization in music: an analysis of songs - Rocha Cruz, Fabielle (Palimpsesto - Revista do Programa de Pós-Graduação em Letras da UERJ, 2024)
Critical Discourse Analysis is an area in constant development, especially with the relevance of multimodal texts, which are becoming increasingly frequent due to the presence of technology. Considering the significance of CDA in applied linguistics and other areas, this article aims to present the concepts of intertextuality and recontextualization through the lens of music, highlighting how many texts draw from and build upon existing works. With the conceptualization of these two essential elements in the area of Critical Discourse Analysis, as well as the understanding of multimodality as texts that use different modes to convey their meanings, the article presents the analysis of excerpts from three songs to demonstrate the applicability in a context diverse and non-academic, as CDA is commonly attributed to research. The results indicate that some songs create meaning by merging lyrics with literary, historical, cultural, and journalistic references inserted into the lyrics through recontextualization and intertextuality.